2001
DOI: 10.2174/0929867013372292
|View full text |Cite
|
Sign up to set email alerts
|

Aryltetralin Lignans: Chemistry, Pharmacology and Biotransformations

Abstract: Podophyllotoxin derivatives like etoposide 7a, etophos 7b, and teniposide 7c are used clinically as potent chemotherapeutic agents for a variety of tumors including small cell lung carcinoma, testicular cancer, and malignant lymphoma. These compounds derived from a series of modifications which converted podophyllotoxin 1a from an entity that interacted with tubulin and blocks mitosis to one that induced a block in late S or early G2 by interacting with topoisomerase II. Synthetic studies on podophyllotoxin de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(55 citation statements)
references
References 65 publications
0
51
0
4
Order By: Relevance
“…Several biological activities, such as anti-tumoral, fungicide, and anti-viral actions, have been attributed to the presence of these compounds, (Ayres & Loike, 1990;Botta et al, 2001;Pan et al, 2009). Shengmai San (SMS), a prescription comprised of Panax ginseng, Schisandra chinensis, and Ophiopogon japonicus, has long been used in traditional Chinese medicine.…”
Section: Lignansmentioning
confidence: 99%
“…Several biological activities, such as anti-tumoral, fungicide, and anti-viral actions, have been attributed to the presence of these compounds, (Ayres & Loike, 1990;Botta et al, 2001;Pan et al, 2009). Shengmai San (SMS), a prescription comprised of Panax ginseng, Schisandra chinensis, and Ophiopogon japonicus, has long been used in traditional Chinese medicine.…”
Section: Lignansmentioning
confidence: 99%
“…The combined organic phases were removed and the crude was redissolved in ethyl acetate (50 mL). The organic phase was washed with distilled water (25 mL), brine (25 mL) and finally dried over anhydrous Na 2 …”
Section: (±)-4-(13-benzodioxol-5-ylmethyl)dihydrofuran-2(3h)-one (21)mentioning
confidence: 99%
“…These secondary metabolites are widely encountered in plant kingdom and present a huge structural diversity normally associated with interesting biological effects, such as antitumoral, fungicide and anti-viral. 1,2 Furthermore, they also show other biological activities against insects and some vertebrates ( Figure 1). 3 Trachelogenin amide A (1, Figure 1) is a dibenzylbutane lignan, isolated from the leaves and stems of Trachelospermum jasminoides.…”
Section: Introductionmentioning
confidence: 99%
“…This suggested that their antitumor properties were due to another mechanism of action: their interaction with DNA. In fact, they induce a block in late phase S or early G2 by interacting with the enzyme topoisomerase II (Botta et al, 2001). DNA topoisomerases are nuclear enzymes which make transient DNA strand breaks, allowing the cell to manipulate the topology of its DNA.…”
Section: Antitumour Aryltetralines: Mechanism Of Actionmentioning
confidence: 99%